Advanced chromatic monitoring - Jones, Gordon R. 1938-; Spencer, Joseph W. (Series in sensors, 2020)
Advanced Chromatic Monitoring provides a major source of information about the novel approach of chromaticity with examples of how chromaticity may be deployed for various monitoring applications. It shows with examples what can be achieved with chromatic methods in producing relevant information with a variety of test techniques and in facilitating the interpretation of complex data about complicated situations. It will be of interest to postgraduates and researchers in a wide breadth of physical disciplines (engineering, medicine, environmental sciences) and those involved with data acquisition and analysis. Key Features: Applicable to a wide range of disciplines (engineering, medical, environmental, etc) and those interested in science, technology, data acquisition and analysis Provides an extrapolation of new knowledge well beyond that covered in existing literature with regard to dealing with complicated forms and sets of data Addresses inspiring and innovative areas of research including environmental, power delivery and medical monitoring About the Editors: Emeritus Professor Gordon R. Jones - founder and former Director of the Centre for Intelligent Monitoring Systems (CIMS), former Head of the Department of Electrical Engineering and Electronics, and former Director of Electric Arcs Research Group at the University of Liverpool. He was awarded the IEEE Education, Science and Technology Achievement Medal (1999). Professor Joe W. Spencer - the present Director of CIMS at the University of Liverpool, having been Head of the Department of Electrical Engineering and Electronics at Liverpool. He is involved in operating a multi-million pound technology transfer unit (Sensor City, Liverpool) with whose establishment he played a major role and with which CIMS has major interactions